Ontology based Web Application Reverse-Engineering Approach - Bouchiha, Djelloul; Malki, Mimoun; Benslimane, Sidi Mohamed (INFOCOMP Journal of Computer Science, 2007)
With the Web’s emergence and generalization in various domains such as economy, commerce, education, culture, etc, the Web application reverse-engineering process becomes necessary in order to facilitate the maintenance of such applications and the evolution towards new Web technology like XML, semantic Web, etc. In this paper, we propose a new approach for the Web application reverse-engineering. The approach is based on ontology and it generates a conceptual schema modelling the Web application. This conceptual schema is rich in semantic but reduced in relation to the global ontology. The proposed approach mainly relies on HTML pages analysis, i.e. to analyse tables, lists, forms, etc. It consists of three successive phases: First, the extraction of useful information from the HTML pages. Second phase is the analysis of the extracted information using the domain ontology. And finally, we generate the corresponding UML conceptual schema.